(untitled) (Journal of Management and Social Sciences, 2022)
Studies have shown that unskilled birth attendants during pregnancy and childbirth are one of the major causes of maternal death especially in developing countries. This study aims to examine the reasons for the patronage of traditional birth attendants’ services among pregnant women and nursing mothers in Kaduna State, Nigeria. A descriptive exploratory study design was used and Qualitative data was collected through the use of a pre-tested interview guide. Ten healthcare providers participated in the study in urban and rural communities of Kaduna State, Nigeria. They included seven officers in charge of primary health centers, one Chief Nursing Officer of a tertiary health institution and one Medical Officer-in-charge of a General hospital. QDA Miner Lite v2.0.6 was used in the analysis of the data. The findings revealed that use of health facilities for antenatal care is higher than that of delivery services in the study area which is attributed to poor health seeking behaviour among women in the study area as a result of ignorance. It is recommended that the government should give public enlightenment on need to utilise healthcare facilities for antenatal care and delivery services. Keywords Unskilled birth attendants, maternal death, Kaduna State, pregnancy and childbirth, utilisation of traditional birth attendants